Racism Seen From a Contextual Biblical Ethical Perspective - Wahyoe Rita Wulandari (Eduvest - Journal of Universal Studies, 2022)
The main issue discussed is about racism. While the formal object is the contextual biblical ethics. The biblical interpretation is limited to the response of Lord Jesus to racism, creation and the genealogy of humankind that made by one blood (Adam). From this genealogy we realize that all humans have a conscience given by the LORD God. A conscience or common sense that gives everyone to do something fairly. The justice of the conscience of the Indonesian nation is called "Bhinneka Tunggal Ika" and Pancasila. This two fondation of our nation are firmly reject to all racism issues. Indonesia is our home, where many races or ethnic groups live in it. Through the values that crystallized in Pancasila, the philosophy base in the Bhinneka Tunggal Ika, unity in diversity, will have to be the common sense in every society relation in Indonesia with mutual respect for one another.